Prevalence of intimidation, harassment, and discrimination in resident physicians: a systematic review and meta-analysis - Anees Bahji (Canadian Medical Education Journal, 2019)
Background: The aim of this study was to establish the prevalence of intimidation, harassment, and discrimination (IHD) reported by resident physicians during their training, to identify factors associated with reported IHD, and to identify adverse sequalae associated with IHD.